Have a Free Video Meeting with one of our friendly tutors.

To solve, begin by multiplying both sides of the first equation by 3. This will make the coefficients of y in each equation an equal value of 3. With 15x + 3y = 63 and x -3y = 9, we can now simply add the...

To get an example of what this question is asking: the expansion of (1+x)^2 can be found by distributing and gives 1+2x+x^2. The coefficient of the x^2 term here would be 1, and for the x^1 term it would ...

Square root of 36 = -6,6

Expand the brackets to get:= 5x + 10 - 18 + 3xThen collect like terms:= 8x-8Take out a common factor:= 8(x-1)

In order to satisfy the condition, must have the 4th toss and 5th toss both being heads. Note that the 3rd toss must be tails as otherwise we would terminate the coin tosses prematurely. This leaves the f...